Molecular Imaging of Thrombosis and Thrombolysis - Hoyle, Brian (MD Conference Express, 2014)
This article discusses the use of a novel probe in the positron emission tomography (PET) molecular imaging of thrombosis and thrombolysis in vivo. Diseases including stroke, coronary artery disease, pulmonary embolism, and deep vein thrombosis are often triggered by the formation of a thrombus. Noninvasive assessment of thrombosis is crucial in diagnoses and to monitor disease progression.